Enhancing quality education through digital literacy: Examining the mediating impact of student engagement among university students in Cambodia - Phon, Samean; Ali, Dhakir Abbas (Edelweiss Applied Science and Technology, 2025)
This study investigates the role of digital literacy in enhancing quality education through the mediating effect of student engagement in Cambodian public universities. Amid growing digital integration in education, the research addresses a critical gap in understanding how digital competencies translate into improved academic experiences and outcomes. Drawing on a quantitative methodology, data were collected from 306 valid student responses across five public universities. The structural equation modeling (SmartPLS 3.0) was used to test four hypotheses linking digital literacy, student engagement, and quality education. The findings reveal that digital literacy significantly influences both student engagement (β = 0.430, p = 0.001) and perceived quality education (β = 0.294, p = 0.001). Additionally, student engagement has a direct positive effect on quality education (β = 0.380, p = 0.001). Mediation analysis further confirms that student engagement significantly mediates the relationship between digital literacy and quality education (indirect effect = 0.163, p = 0.001). The model explains 32.2% of the variance in quality education (R² = 0.322) and 18.2% in student engagement (R² = 0.182). The effect size (f²) analysis revealed that student-engagement (0.172) had moderate influences on the quality education and digital literacy (0.103) had small influences on the quality education. These results underscore the strategic importance of fostering digital competencies and cultivating active student engagement to realize sustainable improvements in higher education. The study offers critical insights for policymakers and educational leaders to align digital transformation with pedagogical practices that promote inclusivity, academic excellence, and lifelong learning.